EFFECT OF SOME GROWTH FACTORS ON GIBBERELLIC ACID PRODUCTION FROM WILD STRAIN OF Fusarium moniliforme - Youis Al-Mashhadany; Nehan Al–Bayati (Mesopotamia Journal of Agriculture)
This study showed that the addition of certain compounds separately such as KH2PO4 , K2SO4 , corn steep liquor or yeast extract had affected gibberellic acid production from wild strain of Fusarium moniliforme. Corn steep liquor at the concentration 0.25 gm/L gave 92.31 mg/L of gibberellic acid, while potassium sulphate at the concentration 0.20 gm/L gave 91.95 mg/L of gibberellic acid, potassium dihydrogen phosphate gave the highest production where reached 93.48 mg/L especially at the concentration 0.5 gm/L, at the concentration 1.5 gm/L yeast extract gave 93.15 mg/L of gibberellic acid. The initial pH for highest production of gibberellic acid was 5.5 . The optimal incubation temperature to produce highest yield of acid was 30° C.